Sharing is not caring: Backward integration of consumers - Christian Spindler; Oliver Woll; Dominik Schober (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2018)
A new type of player occurs in the sharing economy: a vertically integrated consumer who owns production facilities and has direct market access, often termed "active prosumer". The prosumer faces a trade-off between market transaction cost and substantial strategic potential to influence both market demand and supply by her decisions. We discuss optimal marketing and production decisions in light of this trade-off. An empirical application to the German-Austrian electricity market demonstrates substantial incentives for active market participation by recently added decentralized renewables production. Prosumers can achieve considerable profit increases by switching roles of net market supplier or customer.
Keywords: 330; Active Prosumer; Capacity Withholding; Self-Supply; Vertical Integration; Consumer Production; Market Participation Cost